Environment and Development Economics 2014
DOI: 10.1093/acprof:oso/9780199677856.003.0004
|View full text |Cite
|
Sign up to set email alerts
|

An Institutional Analysis of Development Cooperation

Abstract: This report is published in Sida Studies in Evaluation, a series comprising methodologically oriented studies commissioned by Sida. A second series, Sida Evaluation, covers evaluations of Swedish development co-operation. Both series are administered by the Department for Evaluation and Internal Audit, an independent department reporting directly to Sida's Board of Directors. Foreword -Does 'aid' itself create incentives that undermine sustainability? This is the provoking question underlying the present study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 63 publications
0
48
0
2
Order By: Relevance
“…Institutional perspectives have contributed to the study of socio-natural interactions, enhancing our understanding of the problems of common pool resources, environmental hazards, and risk and environmental management (Hotimsky et al 2006). For instance, the scholarship on institutional economics informed a significant body of research on local common property arrangements and multilateral environmental agreements (North 1990;Ostrom 1986;Hanna et al 1996;Loehman and Kilgour 1998;Young 2002;Dolšak and Ostrom 2003;Young 2008;Ostrom 2008a;Ostrom 2010;Ostrom 2011;Ostrom and Andersson 2002). Research on common-pool resources explaining the role of institutions in managing them and the incentives for cooperation (Ostrom 2008b) has demonstrated that global processes and institutions shape local outcomes (Agrawal et al 2008).…”
Section: Conceptualising Institutionsmentioning
confidence: 99%
“…Institutional perspectives have contributed to the study of socio-natural interactions, enhancing our understanding of the problems of common pool resources, environmental hazards, and risk and environmental management (Hotimsky et al 2006). For instance, the scholarship on institutional economics informed a significant body of research on local common property arrangements and multilateral environmental agreements (North 1990;Ostrom 1986;Hanna et al 1996;Loehman and Kilgour 1998;Young 2002;Dolšak and Ostrom 2003;Young 2008;Ostrom 2008a;Ostrom 2010;Ostrom 2011;Ostrom and Andersson 2002). Research on common-pool resources explaining the role of institutions in managing them and the incentives for cooperation (Ostrom 2008b) has demonstrated that global processes and institutions shape local outcomes (Agrawal et al 2008).…”
Section: Conceptualising Institutionsmentioning
confidence: 99%
“…While agency problems are rarely mentioned in the literature on political conditionality, it is well documented that institutional incentives can affect the quality and sustainability of foreign aid (Gibson et al 2005;Martens 2002;Ostrom et al 2002;Svensson 2006). Agency problems arise during aid distribution, because responsibility for disbursement is delegated to agencies whose preferences do not directly align with donor governments (e.g.…”
Section: Delegation and Institutional Incentivesmentioning
confidence: 99%
“…Bush 2015;Gibson et al 2005;Hawkins et al 2006;Martens 2002). We know, for example, that policy conditionality is often not enforced because of a 'pressure to disburse' (Ostrom et al 2002;Svensson 2006). Donor agencies seek to maximize their aid budgets and are therefore incentivized to keep disbursing, even if the recipient fails to meet the conditions of the loan or grant.…”
Section: Delegation and Institutional Incentivesmentioning
confidence: 99%
See 1 more Smart Citation
“…See Ostrom et al (2002), Martens et al (2002), Gibson et al (2005), and Faust and Messner (2010, 260-270) among others; and from the fundamentally critical perspective, see also the authors mentioned in the introduction. Efforts to reform the international aid system -frequently referred to as the Paris/Accra/Busan agenda -form part of the more comprehensive international aideffectiveness agenda, the context in which they gained their momentum in the first place.…”
mentioning
confidence: 99%